On moving targets and magic bullets: Can the UK lead the way with responsible data linkage for health research?. Issue 11 (November 2015) - Laurie, G.; Ainsworth, J.; Cunningham, J.; Dobbs, C.; Jones, K.H.; Kalra, D.; Lea, N.C.; Sethi, N.
Highlights: We explore key elements of good governance in health linkage. Adaptive reflexive governance models are essential. Two examples illustrate how we can achieve standardisation of practice. Distinct elements of governance compiled in a composite fashion tend to challenges. Abstract: Purpose: To provide an overview of essential elements of good governance of data linkage for health-related research, to consider lessons learned so far and to examine key factors currently impeding the delivery of good governance in this area. Given the considerable hurdles which must be overcome and the changing landscape of health research and data linkage, a principled, proportionate, risk-based approach to governance is advocated. Discussion: In light of the considerable value of data linkage to health and well-being, the United Kingdom aspires to design and deliver good governance in health-related research. A string of projects have been asking: what does good governance look like in data linkage for health research? It is argued here that considerable progress can and must be made in order to develop the UK's contribution to future health and wealth economies, particularly in light of mis-start initiatives such as care.data in NHS England. Discussion centres around lessons learned from previous successful health research initiatives, identifying those governance mechanisms which are essential to achieving good governance. Conclusion: This article suggests that a crucial element in any step-increase of research capability will be the adoption of adaptive governance models. These must recognise a range of approaches to delivering safe and effective data linkage, while remaining responsive to public and research user expectations and needs as these shift and change with time and experience. The targets are multiple and constantly moving. There is not – nor should we seek – a single magic bullet in delivering good governance in health research.